Wet-chemical synthesis of solution-processible porous graphene via defect-driven etching. (15th November 2021) - Hu, Yalei; Cao, Qing; Neumann, Christof; Lehnert, Tibor; Börrnert, Felix; Wang, Yiqing; Kaiser, Ute; Turchanin, Andrey; Eigler, Siegfried
Abstract: Etching pores in the basal plane of graphene by wet-chemical methods with a certain size-control reflects a synthetic challenge. Here, a facile and controllable method is presented to produce solution-processible porous-graphene derivatives. The derivative of graphene oxide, here oxo-functionalized graphene (oxo-G) with a controlled density of in-plane vacancy defects is chosen as a precursor. Hydroxyl radicals are generated, which etch pores into the basal plane of oxo-G, preferably starting at defect sites. Thereby, solution-processible flakes of oxo-G with μm-size lateral dimensions and pores with tunable diameters between 5 nm and 500 nm are accessible. Moreover, a plausible mechanism for the growth of pores is proposed based on AFM, TEM, UV–vis spectroscopy, FTIR spectroscopy, XPS, solid-state NMR spectroscopy and statistical Raman spectroscopy. In first approximation, the electrophilic addition and oxidation reaction between hydroxyl radicals and oxo-G close to defect-sites is the basis for etching. The porous graphene materials may act as membranes or tunable two-dimensional materials. Graphical abstract: Image 1 Highlights: A facile and controllable method is presented to prepare solution-processible porous-graphene derivatives. The mechanism of the growth of pores is proposed as a defect-driven process. The as-prepared porous graphene derivatives is a starting point to develop a controlled chemistry at the rims of pores.